The influence of physical exercise on the relation between the phase of cardiac cycle and shooting accuracy in biathlon - Gallicchio, G.; Finkenzeller, T.; Sattlecker, G.; Lindinger, S.; Hoedlmoser, K. (European Journal of Sport Science, 2019)
This study examined the influence of physical exercise on the relation between shooting accuracy and the phase of the cardiac cycle in which the shot is fired. Thirteen experienced biathletes (8 females, mean age 17 years) fired from the standing position at rest and right after a submaximal exercise on a bicycle ergometer. Shooting accuracy and the timing of each shot relative to the R-waves of the electrocardiogram (ECG) were recorded. Best shots (with greatest accuracy) and worst shots (with lowest accuracy) were fired prevalently in different phases of the cardiac cycle. In the rest condition, best shots were fired less frequently from 200 to 300 ms and more frequently from 500 to 600 ms after the R-wave, compared to worst shots. In the exercise condition, best shots were fired less frequently from 100 to 200 ms after the R-wave and from 20% to 30% of the R-R interval, compared to worst shots. These findings support the hypothesis that shooting accuracy is influenced by the cardiac cycle phase due to the ballistocardiac recoil generated at each heartbeat. To achieve best results athletes could be trained (e.g. through biofeedback) to fire within a specific phase of the cardiac cycle.